Catalysts for Building Healthy Societies: Collaboration between Health Social Workers and General Practitioners at the Grassroots Level - LI Yihua, ZHAO Aiyang, ZENG Fei, FANG Xue, ZHANG Wang, WANG Xin (Zhongguo quanke yixue)
To support the advancement of the "Healthy China" policy, is paper delves into the significance of interprofessional collaboration between health social workers and general practitioners in the primary healthcare setting. With a focus on three vital areas, including the synergy of complementary professional knowledge, integration with hospitals and communities, and the expansion of social health research, particularly in strengthening the public health emergency response system and boosting medical alliances. Synergistic efforts between health social workers and general practitioners can serve as a vital component in promoting nationwide health initiatives and fostering healthier societies. Furthermore, this paper proposes countermeasures to address the key challenges surrounding health social work.